Microemulsion electrokinetic chromatography with polarity switching stacking mode for the determination of dexamethasone and dexamethasone sodium phosphate: application to pharmacokinetic studies in rabbit plasma. Issue 7 (7th April 2015) - Maher, Hadir M.; Alzoman, Nourah Z.; Alshehri, Mona M.; Aljohar, Haya I.; Sultan, Maha A.
<x xml:space="preserve">Abstract</x> MEEKC electropherograms of (A) a standard mixture of (2.0 μg mL−1) HCT, (1), DEX-SP, (2), and DEX, (3) and (B) the treated rabbit plasma sample.